Penanaman Mangrove di Pesisir Pantai yang Terdampak Kegiatan Penambangan Nikel di Desa Sopura, Kecamatan Pomalaa, Kabupaten Kolaka - La Ode Dzakir; Rina Rembah; Sahrul Poalahi Salu; Suwarto Sunandar; Arif Arif; Syahrul Syahrul; Isramyano Yatjong; Rizki Kumalasari; Nurfasiha Nurfasiha; Hasriyanti Hasriyanti (ANOA: JURNAL PENGABDIAN MASYARAKAT FAKULTAS TEKNIK, 2023)
Mining activities that take place around Pomalaa District, Kolaka Regency, cause water pollution and sedimentation processes on the coast of Sopura village. Seeing these conditions, the mining engineering study program at Sembilanbelas November University aims to carry out mangrove planting activities on the coast in Sopura village which is affected by nickel mining activities. Based on the results of the activities carried out, it can be concluded that the mangrove planting activities carried out by the mining engineering study program are going well. This is proven by the success of the mining engineering study program in planting 200 mangrove trees on the coast in Sopura Village, Pomalaa District, Kolaka Regency.